Pengaruh Strategi Reading Aloud terhadap Kemampuan Membaca Al-Qur’an Siswa Madrasah Ibtidaiyah - Anggraini , Kiky Chandra Silvia; Fathiyatussholihah, Fathiyatussholihah (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
One of the effects of the lack of fluency and pronunciation of the letters of the Al-Qur’an is the low ability to read. The solution to the low ability to read the Al-Qur'an is to apply the reading-aloud strategy. This study aims to determine the application of reading aloud and the effect of the reading aloud strategy on the ability to read the Al-Qur'an in learning Al-Qur'an Hadith. This research applied a quantitative method of Quasi Experiment type with one group pretest post-test Design. The instrument used is a performance sheet in the form of a reading ability test, which is analyzed with the SPSS test in the form of Paired Sample T-Tes. Based on the study results, the pretest results were lower than the post-test. Based on data analysis to test the research hypothesis, it is known that the significance value is 0.000 <0.05. This study concludes that Ha is accepted and Ho is rejected, so the study's results accept Ha, which reads that the reading aloud strategy affects the ability to read the Al-Qur'an in learning Al-Qur'an Hadith in class III MI Darul Ulum Jotosanur.